Mortality among chemical workers in a factory where formaldehyde was used. Issue 9 (September 1996) - Marsh, G M; Stone, R A; Esmen, N A; Henderson, V L; Lee, K Y
Abstract : OBJECTIVES: An independent and updated historical cohort mortality study was conducted among chemical plant workers to investigate further an association between exposures to formaldehyde and particulates and cancers of the nasopharynx and lung reported in an earlier National Cancer Institute study of the same plant. METHODS: Subjects were 7359 workers who were first employed between 1941 and 1984 in a factory in Wallingford, Connecticut where formaldehyde was used. Vital status was determined on 31 December 1984 for 96% of the cohort and death certificates were obtained for 93% of 1531 known deaths. Exposures of individual workers were estimated quantitatively for formaldehyde, product particulates, and non-product particulates, and qualitatively for pigment. Statistical analyses focused on 6039 white men in 1945-84. Cohort data that could not have been included in the National Cancer Institute study were also analysed separately. RESULTS: Mortality among long term workers (employed > or = 1 y) was generally similar to or more favourable than that of the general population, and there was little evidence of a relation between either rates of lung cancer or standardised mortality ratios (SMRs) and several measures of exposure to formaldehyde, particulates, and pigment. For several causes including lung cancer, death rates among short term workers (employed < 1 y) were significantly increased. Short term workers did not seem to differ from long term workers for the exposures considered. Among all white men, a significant SMR of 550 (local comparison) for nasopharyngeal cancer (NPC) was based on the same four index cases identified in the earlier study of this plant. Only one case of nasopharyngeal cancer had any appreciable exposure to formaldehyde. No new cases of nasopharyngeal cancers were found among the cohort data that could not have been included in the National Cancer Institute study–that is, extended observation time and additional study members. CONCLUSIONS: Among workers employed for at least one year, this study provides little evidence that the risk of lung cancer is associated with exposure to formaldehyde alone or in combination with particulates or pigment. The significant increases in both the rates and SMRs for lung cancer seem to be primarily a phenomenon of short term workers, but the possibility remains that unmeasured occupational or non-occupational factors may have played a part.